MENELUSURI IDEOLOGI MEDIA TEMPO.CO MELALUI KONSTRUKSI REALITAS BERITA AMANDEMEN UUD 1945 - Kurniawan Fadilah; Teguh Tjatur Pramono; Rustono Farady Marta; Joshua Fernando; Endik Hidayat (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
The research will be purposed to review the news regarding amandemends narration created by online media Tempo.co. The qualitative research will use Robert N. Entman’s Framing Analysis model. The results of the research implicate that there are refutation of amandemend narratives of UUD 1945 proposed by People’s Consultative Assembly of Indonesia. The cause of this phenomena lies within the public’s rejection regarding the amandemend due to it’s danger’s posed. Every assembly’s desicion relies on every stakeholder’s perspective, which makes the decision not one sided nor biased. The author recommends to Tempo.co that PPHN and GBHN has to be explained more comprehensively. The amandemend narrative of UUD 1945 offers a room for both the people’s assembly and Indonesians, which involve interviewees of both sides to create the news article. Tempo.co has to maintain the balance and accuracy of news production as it stands with their ideology.